Effects of the concentration of plasma platelet on the cryopreservation of ram semen - Sitó-Silva, Luan [UNESP] (2025)
The objective of this study is to assess the effect of autologous platelet-rich plasma (PRP) and platelet-poor plasma (PPP) on the cryopreservation of ovine semen. Eight rams were used, previously trained for collection using an artificial vagina. The collected semen was separated into five parts and diluted in Botubov® (Botupharma, Botucatu, Brazil), and five treatments were tested: Control (pure commercial semen extender); PRP10 (Extender supplemented with 10 million platelets/mL); PRP20 (Extender supplemented with 20 million platelets/mL); PRP40 (Extender supplemented with 40 million platelets/mL); and PPP (Extender supplemented with PPP in the same volume used for PRP40). The semen was then packaged in French straws, cooled for 3 h at 5 °C, and frozen in liquid nitrogen until evaluation. Kinetic parameters were evaluated using computer-assisted sperm analysis (CASA), immediately post-thaw and after a 3-h thermoresistance test at 37 °C, as well as assessment of plasma membrane and acrosomal integrity (PMAI), mitochondrial potential (MP), superoxide anion (O2) production, and hydrogen peroxide (H2O2) production by flow cytometry. Both PRP and PPP were shown to be safe for the cryopreservation of ram semen, with improvements observed in half of the animals in terms of flow cytometry parameters. When grouped together, it was evident that the PPP group displayed greater integrity of the plasma membrane and acrosome (P = 0.02), more stable cells (P = 0.03), and increased production of H2O2 (P = 0.05). In conclusion, PRP and PPP are safe and can be viable additives for freezing ram semen. PPP showed better results for plasma and acrosomal membrane integrity, as well as the number of stable cells in half of the animals. This highlights PPP as a promising antioxidant and cryoprotectant for ram semen.